Twenty-one new species of the Neotropical rove beetle genus Neolindus Scheerpeltz (Coleoptera, Staphylinidae, Paederinae) - Guzman, Yoan Camilo; Tokareva, Alexandra; Koszela, Katarzyna; Żyła, Dagmara (European Journal of Taxonomy, 2024)
Rove beetles (Staphylinidae) are a diverse insect group, especially in the Neotropical region. At the same time, this fauna remains significantly understudied. During our visits to museum collections, we encountered numerous specimens of undescribed species representing the Neotropical genus Neolindus Scheerpeltz, 1933 which was earlier thought to be rare. To address the knowledge gap in the genus, we studied the museum material that resulted in descriptions of 21 new species. Our work involves the redescription of the genus, descriptions of the new species, and an updated identification key to 39 previously described and new species. The newly described species are Neolindus bicornis Guzman, Tokareva & Żyła sp. nov., N. elegans Guzman, Tokareva & Żyła sp. nov., N. longithorax Guzman, Tokareva & Żyła sp. nov., N. luxipenis Guzman, Tokareva & Żyła sp. nov., N. maya Guzman, Tokareva & Żyła sp. nov., N. minutus Guzman, Tokareva & Żyła sp. nov., N. napo Guzman, Tokareva & Żyła sp. nov., N. niger Guzman, Tokareva & Żyła sp. nov., N. ornatus Guzman, Tokareva & Żyła sp. nov., N. parahermani Guzman, Tokareva & Żyła sp. nov., N. paraplectrus Guzman, Tokareva & Żyła sp. nov., N. parasinuatus Guzman, Tokareva & Żyła sp. nov., N. parautriensis Guzman, Tokareva & Żyła sp. nov., N. pseudosensillaris Guzman, Tokareva & Żyła sp. nov., N. sauron Guzman, Tokareva & Żyła sp. nov., N. sibyllae Guzman, Tokareva & Żyła sp. nov., N. triangularis Guzman, Tokareva & Żyła sp. nov., N. tropicalis Guzman, Tokareva & Żyła sp. nov., N. utriensis Guzman, Tokareva & Żyła sp. nov., N. volkeri Guzman, Tokareva & Żyła sp. nov., and N. yotokae Guzman, Tokareva & Żyła sp. nov. This research emphasises the importance of museum collections in advancing taxonomy and enriching biodiversity knowledge. With these contributions, the known number of species of Neolindus reaches 60, thereby enhancing data on the Neotropical rove beetles diversity. Additionally, we provide several new country records for the genus (Guyana, Mexico, Nicaragua, and Suriname), which widen its distribution, and new occurrence records for the described species of Neolindus, N. agilis Herman, 1991; N. apiculus Herman, 1991; N. basisinuatus Herman, 1991; N. campbelli Herman, 1991; N. cuneatus Herman, 1991; N. hermani Asenjo, 2011; N. irmleri Asenjo, 2011; N. lodhii Herman, 1991; N. procarinatus Herman, 1991; N. punctogularis Herman, 1991; and N. retusus Herman, 1991.